2020
DOI: 10.4014/jmb.1911.11006
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Biosynthetic Pathway of Vitamin B Groups and Potential Secondary Metabolite Gene Clusters Via Genome Analysis of a Marine Bacterium Pseudoruegeria sp. M32A2M

Abstract: The symbiotic nature of the relationship between algae and marine bacteria is well-studied among the complex microbial interactions. The mutual profit between algae and bacteria occurs via nutrient and vitamin exchange. It is necessary to analyze the genome sequence of a bacterium to predict its symbiotic relationships. In this study, the genome of a marine bacterium, Pseudoruegeria sp. M32A2M, isolated from the southeastern isles (GeoJe-Do) of South Korea, was sequenced and analyzed. A draft genome (91 scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Most importantly, P. coloniale is also a vitamin B 7 (biotin) auxotroph, lacking all four genes involved in the biosynthesis of this vitamin, and apparently the only biotin auxotroph currently known among Archaeplastida 82 (Supplementary Table 21). Many genomes of marine bacteria contain full sets of biotin biosynthesis genes 83,84 and these bacteria could be a source of biotin for P. coloniale. Genome compaction in these picoplanktonic eukaryotes may have facilitated evolution of such symbiotic interactions in an oligotrophic marine environment.…”
Section: De Novo Nad + and Quinolate Biosynthesis In P Colonialementioning
confidence: 99%
“…Most importantly, P. coloniale is also a vitamin B 7 (biotin) auxotroph, lacking all four genes involved in the biosynthesis of this vitamin, and apparently the only biotin auxotroph currently known among Archaeplastida 82 (Supplementary Table 21). Many genomes of marine bacteria contain full sets of biotin biosynthesis genes 83,84 and these bacteria could be a source of biotin for P. coloniale. Genome compaction in these picoplanktonic eukaryotes may have facilitated evolution of such symbiotic interactions in an oligotrophic marine environment.…”
Section: De Novo Nad + and Quinolate Biosynthesis In P Colonialementioning
confidence: 99%
“…Similarly, Pseudoruegeria is associated with algae. Algae produces dissolved organic matter, oxygen, and sulfur, and the bacteria supplies the algae with the vitamins thiamin, biotin, and cobalamin (Cho et al, 2020). As mentioned before, tube tops contain plant material and algae, so it is not surprising genera associated with algae and sea grasses are enriched in tubes.…”
Section: Distinct Microbiomes Of Tubes and Sedimentmentioning
confidence: 95%
“…Bacteroidetes and Verrucomicrobia were associated with diatoms (Bruckner et al, 2008), and Latescibacteria are also associated with algae cells (Youssef et al, 2015). More specifically, Granulosicoccus have been isolated from seagrass (Kurilenko et al, 2010) and algae (Park et al, 2014), while Pseudoruegeria supplies algae with thiamin, biotin, and cobalamin (Cho et al, 2020), and Maribacter is found on the surface of macroalgae (Bakunina et al, 2012). Worms have been shown to collect algae and use it as building material to add structure to the tube tops (Berke et al, 2006;Berke, 2012) and may serve as a direct food supply for omnivorous worms (Magnum et al, 1968) or as an indirect food supply when the worm eats the algae-associated meiofuana (Bell and Coen, 1982).…”
Section: Potential Biogeochemical Processes In Tubesmentioning
confidence: 99%
“…•s −1 photons at 20 • C ± 1 • C. Pseudoruegeria sp. M32A2M was isolated from surface water of the South Sea in South Korea, where HABs of Alexandrium are frequently observed (Cho et al, 2020). Pseudoruegeria sp.…”
Section: Cell Culturementioning
confidence: 99%